1991
DOI: 10.7863/jum.1991.10.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Doppler sonography in renal parenchymal disease. Histopathologic correlation.

Abstract: To evaluate the histopathologic changes influencing Doppler measurements of the resistive index (RI) in renal arteries in renal parenchymal diseases, 68 kidneys in 34 consecutive patients with various forms of renal parenchymal diseases were studied by duplex Doppler ultrasound (duplex US) immediately before percutaneous renal biopsy. The RI, renal length, and renal cortical echogenicity were correlated with the amount of glomerular, interstitial, and vascular changes graded on a scale from 0 to 100. The renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
111
1
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 18 publications
11
111
1
7
Order By: Relevance
“…16 Such an increase in blood flow may result in glomerulosclerosis and the glomerulosclerosis may be associated with elevated RI values in the remaining kidney. 20 Another notable result in our study was the absence of any significant difference between RI values of right remnant kidney in cases of left nephrectomy and those of left remaining kidney in cases of right nephrectomy. To our knowledge, there is no reported study dealing with such a comparison.…”
Section: Discussionsupporting
confidence: 47%
“…16 Such an increase in blood flow may result in glomerulosclerosis and the glomerulosclerosis may be associated with elevated RI values in the remaining kidney. 20 Another notable result in our study was the absence of any significant difference between RI values of right remnant kidney in cases of left nephrectomy and those of left remaining kidney in cases of right nephrectomy. To our knowledge, there is no reported study dealing with such a comparison.…”
Section: Discussionsupporting
confidence: 47%
“…In our study, we found that the echogenicity of renal parenchyma and cortex were both equally and grossly increased in acute, chronic and end-stage parenchymal diseases. Increased echogenicity of renal cortex has proven to be significantly related to various parenchymal pathological changes such as tubular atrophy, fluid retention, arteriosclerosis and hyaline cylinders [11] [12]. Fiegler et al [13] reported that the echogenicity of the renal parenchyma was correlated with glomerular and interstitial findings.…”
Section: Discussionmentioning
confidence: 99%
“…An increased carotid IMT is a wellknown marker of subclinical atherosclerosis, and strongly predicts the occurrence of myocardial infarction and stroke [7,15]. Furthermore, increased intra-renal RI and PI values also reflect end-organ damage, characterized by glomerular and arteriolar sclerosis [16]. Increased intra-renal resistances might indicate, at least at an early stage, a functional and reversible modification consequent to intra-renal vasoconstriction due to endothelial dysfunction [11].…”
Section: Introductionmentioning
confidence: 99%